Mapping the Expertise and Understanding of Menarche, Menstrual Hygiene, and Menstrual Health among Adolescent Ladies in Low- and Center-Profit Nations - Rehan Haider (International Journal of Integrative Sciences, 2023)
Many adolescent girls begin their periods uninformed and unprepared; moms are the primary supply of facts, however, they tell girls, too-little and too past due and regularly speak their misconceptions and due to the fact menstruation is widely visible as polluting and shameful, girls are often excluded and shamed in their houses and their groups. Many no longer have the manner for self-care and no longer get the help they need when they face issues, which averts their potential to hold on with regular activities and can also set up a basis for lifestyles-long dis empowerment. Efforts to respond to girls’ needs have been fragmented and piecemeal. There is a growing acknowledgment that efforts are much more likely to be successful if they come together in an entire-of-community technique that includes schools, fitness centers, and houses and communities; educate girls about menstruation, Create norms that see menstruation as healthful and nice, no longer shameful and dirty, enhance get admission to sanitary products, strolling water, and functional bathrooms and privateness for self-care, enhance care for and aid with the aid of ladies’ families after they have their periods, enhance access to in a position and caring medical experts once they experience menstrual health troubles